Socio-political conditions of desire’s freedom in Spinoza and Hegel - Çelik, Olcay. (Thesis (M.A.) - Bogazici University. Institute for Graduate Studies in Social Sciences, 2014., 2014)
In Spinoza and Hegel desire is defined as the very essence of everything and their philosophies provide us a perspective through which we can understand that the movements of our thoughts and bodies are taken actually movements of our desire. Besides, for both philosophers, freedom of desire can only be attained in an empowering social and political context. At this point, Spinoza and Hegel provide two different accounts of how desire becomes free in a socio-political structure. In Hegel, liberation is a process that starts with self-interested people’s struggle for recognition and reaches its climax in a society where different subjective wills, needs and abilities of people are integrated with each other through time and finally constitute a socially stratified Ethical Life in which every individual knows, wills and acts accordingly to the universal will. When it comes to Spinoza, we see that desire can become freer insofar autonomous individuals increase their joy by focusing on the commons. In this manner, Spinoza’s system suggests a political strategy, which eliminates unequal social conditions that make people torn by affects while Hegel takes differences as the basis and thus, freedom requires the integration of social classes that emerge from natural differences among people. Hence, it can be said that unlike Hegel’s recognition model that takes actual identity of individuals as given, Spinozian recognition focuses rather on what one can become. This suggests that Spinozian recognition model serves better for constitutive politics in practice because its socio-political ontology of desire always reminds us our being structures with a capacity to rebuild ourselves in a more liberatory way and avoid the risk of assuming asymmetrical subjection as freedom.